2014
DOI: 10.1128/jcm.01678-14
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Long-Read 16S Sequencing To Characterize the Lung Microbiome from Mechanically Ventilated Patients with Suspected Pneumonia

Abstract: iIn critically ill patients, the development of pneumonia results in significant morbidity and mortality and additional health care costs. The accurate and rapid identification of the microbial pathogens in patients with pulmonary infections might lead to targeted antimicrobial therapy with potentially fewer adverse effects and lower costs. Major advances in next-generation sequencing (NGS) allow culture-independent identification of pathogens. The present study used NGS of essentially full-length PCRamplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 45 publications
3
58
3
Order By: Relevance
“…This is in line with previous studies that report that the respiratory microbiome is disturbed markedly during pneumonia 29 30. We extend the finding of the limited studies done in ICU-patients,25 31 32 as no control group was included in those studies and thus it was previously unknown what the ‘normal’ dynamics in the respiratory microbiome were during mechanical ventilation. One excellent study that did include a control group was performed in young and elderly non-critically ill patients 29.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with previous studies that report that the respiratory microbiome is disturbed markedly during pneumonia 29 30. We extend the finding of the limited studies done in ICU-patients,25 31 32 as no control group was included in those studies and thus it was previously unknown what the ‘normal’ dynamics in the respiratory microbiome were during mechanical ventilation. One excellent study that did include a control group was performed in young and elderly non-critically ill patients 29.…”
Section: Discussionsupporting
confidence: 89%
“…Toma et al compared the microbiota of endotracheal aspirates from intubated adults with possible ventilator-associated pneumonia and found no differences in diversity when comparing low and high-risk groups as per the Clinical Pneumonia Infection Score (CPIS). 56 However, there were no significant differences between groups in most of the items included in the CPIS, and the authors did not report clinical outcomes at the end of the admission, raising concerns of misclassification. Wang et al compared the microbiota of bronchoalveolar lavage fluid in children with pneumococcal and Mycoplasma pneumonia with controls, and reported that controls had the lowest microbial diversity.…”
Section: Pneumonia and Ventilator-associated Pneumoniamentioning
confidence: 97%
“…Culture-dependent and culture-independent analyses of BAL from pneumonia patients are usually well aligned, although we have identified rare instances of culture-negative pneumonia (12). Although an adequate depth of sequencing can identify numerous additional bacterial species in the BAL of pneumonia patients (124, 125), the dominant pathogenic species generally composes the vast majority (74% or more) of detected sequences. Some long-assumed beliefs about the microbiology of pneumonia are still true: Most pneumonia is caused by a single pathogen, and most (but not all) pathogens are effectively identified by bacterial culture.…”
Section: The Microbiome Of the Diseased Lungmentioning
confidence: 99%